Deconstructing Stigmatisation by Heterosexuals of LGBT Against the Backdrop of Religion in Malaysia - Sharifah Sophia, Wan Ahmad; Ting, Su Hie; Collin, Jerome; Yeo, Jiin Yih (Asia-Pacific International University, 2023)
The study focussed on deconstructing heterosexuals’ stigmatisation of LGBT in the context of religion in Malaysia. The qualitative study involved semi-structured interviews with 21 heterosexuals (Buddhist, Christian, Muslim). The interview questions focussed on societal and personal views of LGBT. Thematic analysis of interview transcripts totalling 30,488 words showed the lay perspective on the construction of homosexuality interms of personal choice, situational factors, and ideologies of stigma. The participants were able to empathize with personal choice only because they perceived the LGBT individuals had no chance of reverting to a so-called normal identity. The participants re-animated, rehearsed and re-presented the ideological defence of heterosexuality through repeated stigmatisation of difference and non-conformity in the context of the normative religious beliefs. They also perceived homosexuals as a potential threatto the morality of the norm-compliant population, prone to emotional and psychological instability, and a threat to the veneer of normalcy. The study showed that such popular theorising is not a neutral instrument of knowledge but one that carries ideological power in normalizing stigma towards LGBT